Pendampingan Materi Dasar Morphology On ELT Melalui Media Lagu Bagi Siswa Kelas VIII Di MTS Hidayatul Insan Palangka Raya - Siti Anisah; Zaitun Qamariah; Akhmad Ali Mirza; Abdul Syahid (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
This community service activity aims to increase the understanding of class VIII students at MTs Hidayatul Insan, Palangka Raya, regarding the basic material of Morphology in teaching English as a Foreign Language (ELT) through song media. The mentoring method involves presenting basic Morphology material through song lyrics that are relevant to the concept being taught. The results of the service showed a significant increase in students' understanding of the material, as well as a positive response to the use of songs as a learning medium. Keywords: Community service, Morphology, English as a Foreign Language (ELT), mentoring, song media.